PERANCANGAN CORPORATE IDENTITY TAMAN WISATA PAGGORA SEBAGAI UPAYA MENINGKATKAN BRAND LOYALTY - Hidayati, Fitria Nurul (Jurnal Art Nouveau, 2014)
Abstract: âTAMAN WISATA PAGGORAâ is a first tourist place established as a means of education, sports, arts and social activities in Kediri. âTAMAN WISATA PAGGORAâ stand by the ideals of a nation-building efforts in the field of Education, Sport, Arts and Social on July 14, 1961 initiated by Soekertijo (deceased with the rank of Major General TNI) and Lt. Col. Tjokrokoesoemo Ruler (deceased with the rank of Major General TNI) along the entire Kediri community elements inspired by the mandate of the Great Commander General Sudirman and the nature of the military as the Peoples Army. Loyalty Traveler is very good at the beginning, but at the moment it has decreased due to the lack of a clear identity for the promotion to be effective, it is necessary to design corporate identity in accordance with the vision and mission of it to be applied to a logo so it can be applied into various other media to promote the good and able to increase Brand Loyalty.